Pengaruh Small Side Game melalui Interval, Pyramid dan Mix Method Training terhadap Peningkatan Speed 30m Pemain Sepakbola (Jurnal Simki Pedagogia, 2025)
This study aims to analyze the effect of training with interval, pyramid, and mix methods in small sided game (SSG) on increasing 30-meter speed. This study uses a quantitative design with a pre-test and post-test approach to compare the three training methods. The research sample consisted of 30 male soccer athletes aged 17 to 18 years from the Persib Bandung Academy who followed a 6-week training program. Sampling was carried out using a simple random sampling technique. The data collected were analyzed using parametric statistics, after passing the normality, homogeneity, and paired sample t-test tests by showing results that met the requirements. The results showed that there was no significant difference between the interval, pyramid, and mix training groups in increasing 30-meter running speed.